Weekend and evening planned colonoscopy activity: a safe and effective way to meet demands - Afify, Shimaa A.; Abo-Elazm, Omnia M.; Bahbah, Ishak I.; Thoufeeq, Mo H. (Endoscopy International Open, 2021)
Background and study aims Colonoscopy is the “gold standard” investigation for assessment of the large bowel that detects and prevents colorectal cancer, as well as non-neoplastic conditions. The Joint Advisory Group (JAG) on Gastrointestinal Endoscopy recommends monitoring key performance indicators such as cecal intubation rate (CIR) and adenoma detection rate (ADR). We aimed to investigate the quality of colonoscopies carried out during evening and Saturday lists in our unit and compare them against JAG standards of quality for colonoscopies.Patients and methods We retrospectively collected and analyzed demographical and procedure-related data for non-screening colonoscopies performed between January 2016 and November 2018. Evenings and Saturdays were defined as the out-of-hour (OOH) period. We compared the outcomes of the procedures done in these against the working hours of the weekdays. We also wanted to explore whether the outcomes were different among certain endoscopists. Other factors that could affect the KPIs, such as endoscopist experience and bowel preparation, were also analyzed.Results There were a total of 17634 colonoscopies carried out; 56.9 % of the patients (n = 10041) < 70 years old. Key Performance Indicators (KPIs) of weekday, evening, and Saturday colonoscopies regarding the CIR and ADR met the JAG standards as they were above 93 % and 24 %, respectively. Advanced colonoscopists had better KPIs when compared to the non-advanced colonoscopists, with CIR at 97.6 % vs. 93.2 % and ADR at 40.8 % vs. 26 %, respectively. Conclusions JAG standards were maintained during colonoscopies done on weekdays, evenings, and Saturdays. Advanced colonoscopists had higher CIR and ADRs.